INFECTION OF URINARY TRACT IN MENOPAUSAL WOMEN - Smjesko Gordana (Sanamed, 2019)
Urinary infections are, by frequency, in the second place, immediately behind respiratory infections. The prevalence of urinary tract infections is generally increasing. UTI (urinary tract infections) is more common in women and very young people. The rates of occurrence generally reflect predisposing factors such as congenital anomalies in childhood, the onset of sexual activity, especially in women, and, of course, postmenopausal changes in older women. It is assumed that 50-60% of women can expect an episode of urinary infection during their lifetime. In postmenopausal women, there is a deficit in estrogen. It is one of the important factors that indirectly protects the vaginal mucous membranes as well as the uroepitel from infection. Bacteria from the digestive tract colonize the skin of the perineum, then the vulva, the vagina and the outer opening of the urethra. Normal vaginal flora (lactobacilli) protects the vagina from colonization by fecal bacteria because it lowers pH and creates unfavorable conditions for survival of bacteria.